THE LEADERSHIP OF TWO CHARACTERS IN TRANSFORMERS MOVIE - Hardiantoro, Baruna; Kuncara, Singgih Daru; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
This research studied the character of two leaders in Transformers movie.  There are six movies of Transformers, but the writer only took four movies squeal as the object research is because the changed story and character in the fifth and the sixth movies. The subject of this research is Optimus and Megatron character. There are two objectives in this research, the first is the leadership of two leaders and the second is the character of two leaders. The writer used the leadership theory into three categories the first category is Dilts’ model of leadership, the second category is Davis’ form of leadership theory and the third category is Stogdill’s characteristic of leadership. Meanwhile to find the character of two leaders, the writer used Johnson’s indirect characterization theory that consists of five methods namely is speech, thoughts, effect to other characters, action and looks. This research is categorized as descriptive qualitative that consists to data in the form of words and sentences. The data are dialog of script in movie.  The results of this study, the writer found the different leadership and character two leaders. The writer found their characters and leaderships by seeing the interaction between leader and follower in movies. Optimus Prime’s leadership categorizes in macro leadership, leadership positive form and all of leadership characteristic. Optimus characters defined as moral character. Meanwhile Megatron’s leadership categorizes in meta leadership, leadership negative form and all of leadership characteristic. Megatron characters defined as immoral character.